SOCIAL SUPPORT, COMMUNITY CULTURE, AND RECEIPT OF HEALTH INFORMATION ON MATERNAL COMMITMENT TO PREVENT STUNTING IN CHILDREN UNDER FIVE IN BANGKALAN DISTRICT - Fitriah; Mustofa Haris; Rodiyatun; Suryaningsih (Kirana Publisher, 2024)
Stunting cases, which are a threat to the growth of toddlers, are still very high in Bangkalan Regency. The purpose of the study was to analyse the influence of social support, community culture and information acceptance on maternal commitment to stunting prevention. This research is a survey research with a cross sectional approach. The target population in this study were mothers who had toddlers 2-4 years old in Bangkalan Regency with a total sample of 300 mothers from 5 villages. The sampling technique used was Cluster Random Sampling. Clusters are based on villages with the highest and lowest number of stunting. The data collection instrument used a questionnaire. The variables studied were social support, community culture and receipt of health information as independent variables. While the dependent variable is maternal commitment in stunting prevention. The data obtained in this study were analysed descriptively and then analysed using multiple linear regression tests. Before testing the regression equation model, classical assumption testing was carried out first. The results showed that social support, community culture and information acceptance had an effect on maternal commitment in preventing stunting both partially and simultaneously with a significance level of 0.000. The existence of social support will give rise to self-confidence and increase the mother's commitment to provide better care to children so that stunting does not occur. Through culture, values, beliefs, norms, and practices that are considered important by a community group and become individual commitments, including efforts to prevent stunting. Receiving information will build mothers' attitudes and beliefs about their ability to prevent stunting, as a form of maternal commitment.